36 Years of Subsidence Reporting at the ICGCM - Anthony T. Iannacchione; Nicole E. Evanek (International Conference on Ground Control in Mining, 2018)
"Over the past 36 years, a great deal of information has been presented and discussed at the International Conference on Ground Control in Mining (ICGCM). The topic of surface subsidence engineering has resonated throughout each of the 36 conferences, producing 155 related papers. These papers have come from many countries. The major focus has been underground coal, especially longwall mining, but hard rock mining has also received attention. This impressive collection of reports presents a unique opportunity to reflect on the progress made towards understanding subsidence basin characteristics and developing methods to predict and mitigate its impact.In the initial meetings, the focus was on measuring subsidence and developing prediction methods. As understanding increased, predictive methods were developed and tested, especially in North America, China, Australia, Europe, and India. Efforts were made to understand how structures, aquifers, and surface waters were impacted by the formation of subsidence basins. As time progressed, the number of papers dropped slightly and became more focused on site-specific conditions. Most recently, advanced monitoring techniques have revealed new information, spurring a resurgence in research activity. Another recent focus has been on anomalous horizontal deformations occurring in sites with significant relief. Several reports from Australia and one from the US have brought this issue to light. In closing, all of these surface subsidence engineering papers have chronicled the maturing of this most important topic and, in the process, highlighted the importance of the ICGCM in the evolution of our current state of practice.INTRODUCTIONThe aim of this paper is to examine the role of ICGCM in 1) shaping our understanding of the mining induced subsidence phenomena, 2) developing tools to help predict its impact on the surface, and 3) evaluating controls to mitigate these impacts.This analysis involved the consideration of 155 papers available within the ICGCM conference proceedings and listed under the subsidence topic. Three of the papers where only available as abstracts and were not included in this analysis. Four other reports were focused on topics other than underground coal mining-induced subsidence issues and were also not included. It should also be noted that papers dealing with overburden behavior were not included in this analysis. As a result, 148 papers were reviewed and analyzed (Figure 1)."